The Relationship Between Body Mass Index, Percent Body Fat, And Belly Fat With U23 Futsal Athlete Fitness - Diyananda, Dzulfiqar; Irawan, Andri; Hasibuan, Muchtar Hendra; Haslim, Alfonsius Billy Joe (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
The purpose of this study was to determine the relationship between BMI, body fat, and physical fitness in U23 futsal players. The data collection method was carried out through a survey using purposive sampling on the University of Indonesia futsal team and Pivot FC totaling 44 participants. The value of aerobic capacity is measured by a bleep test. BMI, body fat, and visceral fat values were measured using the BIA (bioelectrical impedance analysis) method. Spearman rank correlation test results (1) There is a correlation between BMI and physical fitness r = -0.422, significance P value = 0.002 (2) There is a correlation r = -416 between body fat and physical fitness, Significance P value = 0.003 (3) There is a relationship between visceral fat and physical fitness of r = -400, with a significant P value of 0.004. The results of the analysis using multiple correlation UI with linear regression showed that BMI, body fat, and visceral fat had a simultaneous influence of R = 0.521(3) which is a moderate influence.